Socio-spatial features of neighbourhoods supporting social interaction between locals and migrants in peri-urban China - Linyan Dai; Xin Sheng; Rangan Gupta (Journal of Urban Management)
Western literature shows evidence of a positive relationship between socio-spatial features of neighbourhoods and social interaction. However, there is little research exploring this relationship in the Chinese context, particularly between locals and migrants in peri-urban China where significant housing is being created. This paper studies the socio-spatial features of neighbourhoods in supporting social interaction between locals and migrants across different neighbourhood types in the peri-urban areas in Guangzhou. In this research, data were collected using door-to-door questionnaires and site surveys in 9 peri-urban neighbourhoods in Guangzhou. The nature and strength of relationships between socio-spatial features of neighbourhoods and social interaction were examined through statistical analysis. The results of this study suggest that the level of maintenance and accessibility can help improve social interaction for locals and migrants living together in villages, redeveloped villages, and commodity housing. Neighbourhood boundaries and quality of neighbourhoods were found to be positively related to social interaction for locals and migrants in redeveloped villages only. In addition, the perceived character of the neighbourhood can positively impact social interaction for locals in villages only. This study demonstrates that high-quality neighbourhoods can improve social interaction between migrants and locals in peri-urban villages, commodity housing, and redeveloped villages in China. The study provides a guide for neighbourhood designers, urban planners, and property managers in peri-urban China regarding how to create a neighbourhood supporting social interaction between locals and migrants in villages, redeveloped villages and commodity housing respectively.